Distributed magnetic attitude control for large space structures. (September 2022) - Robb, Bonar; McRobb, Malcolm; Bailet, Gilles; Beeley, James; McInnes, Colin R.
Abstract: The utility of distributed magnetic torque rods for the attitude control of a large space structure is investigated. Distributed arrays of actuators offer advantages such as distributing structural loads, increasing fault tolerance, allowing structures to be designed modularly, and additionally the actuators may be integrated with on-orbit fabrication strategies. First, distributed torques are shown to effectively rotate highly flexible structures. This is compared with torques applied to the centre-of-mass of the structure, which cause large surface deformations and can fail to enact a rotation. This is demonstrated using a spring–mass model of a planar structure with embedded actuators. A distributed torque algorithm is then developed to control an individually addressable array of actuators. Attitude control simulations are performed, using the array to control a large space structure, again modelled as a spring–mass system. The attitude control system is demonstrated to effectively detumble a representative 75 × 75 m flexible structure, and perform slew manoeuvres, in the presence of both gravity-gradient torques and a realistic magnetic field model. Highlights: Magnetorquers are investigated for the attitude control of large spacecraft. A spring–mass model of a large, flexible structure is presented. Distributed magnetorquer arrays are found to reduce structural deformations. An algorithm for torque distribution is presented. Orbital simulations of slew manoeuvres are used to demonstrate the strategy.